The Associations Between Clinical Respiratory Outcomes and Ambient Wildfire Smoke Exposure Among Pediatric Asthma Patients at National Jewish Health, 2012–2015. Issue 6 (3rd June 2019) - Lipner, Ettie M.; O'Dell, Katelyn; Brey, Steven J.; Ford, Bonne; Pierce, Jeffrey R.; Fischer, Emily V.; Crooks, James L.
Abstract: Wildfires are a growing threat in the United States. At a population level, exposure to ambient wildfire smoke is known to be associated with severe asthma outcomes such as hospitalizations. However, little work has been done on subacute clinical asthma outcomes, especially in sensitive populations. This study retrospectively investigated associations between ambient wildfire smoke exposure and measures of lung function and asthma control, Forced Expiratory Volume in 1 Second (FEV1) and the Asthma Control Test (ACT) and Children's Asthma Control Test (CACT) test scores, during nonurgent clinic visits. The study population consisted of pediatric asthma patients (ages 4–21; n  = 1, 404 for FEV1 and n  = 395 for ACT/CACT) at National Jewish Health, a respiratory referral hospital in Denver, Colorado, and therefore represents a more severe asthma phenotype than the general pediatric asthma population. Wildfire smoke‐related PM2.5 at patients' residential ZIP codes was characterized using satellite‐derived smoke polygons from NOAA's Hazard Mapping System combined with kriging of ground‐based U.S. EPA monitors. Mixed effect models were used to estimate associations between clinical outcomes and smoke PM2.5 exposure, controlling for known risk factors and confounders. Among older children aged 12–21 we found that wildfire PM2.5 was associated with lower FEV1 the next day but higher FEV1 the day after. We found no associations between wildfire PM2.5 and FEV1 in younger children or between wildfire PM2.5 and asthma control measured by the ACT/CACT in all ages. We speculate that rescue medication usage by older children may decrease respiratory symptoms caused by wildfire smoke. Key Points: We found that lung function in older asthmatic children first decreased then increased following wildfire PM2.5 exposure We found no associations between wildfire PM2.5 and self‐reported asthma control over the prior 30 days We speculate that asthma rescue medication was successful in counteracting the short‐term impact of wildfire PM2.5 among older children